Visitors’ profile at Genting Premium Outlet Genting Highlands - Md Haruji, Nur Faiqah (2018)
Genting Premium Outlet (GPO) is the first hilltop premium outlet in South East Asia. As a newly launched in June 2017, the management should do deeper research on their visitors‟ as it can maximize the revenue of GPO. This study was conducted to identify the profile of the visitors at GPO. The related information of visitors profile such as social demographic, trip characteristics, travel behavior and purchase behavior were collected from 180 respondents including local and foreign visitors by using simple random sampling technique. The data gathered were analyzed using descriptive analysis for the social demographic and trip characteristics of visitors. T-test and Mann Whitney U Test was used to examine differences between foreign and local visitors‟ purchasing behavior. The results show that the highest number of average monthly income was RM 2,000-RM 10,000 and it is considered that they have purchasing power and can afford to purchase branded products offered at GPO. Significant difference was observed between local and foreign visitors‟ in term of travel behavior. Other than that, significant difference between local and foreign visitors‟ in term of purchasing behavior was observed. The findings of this study provide an understanding for local and foreign visitors‟ profiles and the information is essential for the management and marketers to promote GPO and produce effective planning for the future.